Ionospheric response to solar and interplanetary disturbances: a Swarm perspective - Balasis, G.; Papadimitriou, C.; Boutsi, A. Z. (Philosophical transactions of the Royal Society of London. Series A: Mathematical, physical, and engineering sciences, 2019)
The ionospheric response to solar and interplanetary disturbances has been the subject of intense study for several decades. For 5 years now, the European Space Agency's Swarm fleet of satellites surveys the Earth's topside ionosphere, measuring magnetic and electric fields at low-Earth orbit with unprecedented detail. Herein, we study in situ the ionospheric response in terms of the occurrence of plasma instabilities based on 2 years of Swarm observations. Plasma instabilities are an important element of space weather because they include irregularities like the equatorial spread F events, which are responsible for the disruption of radio communications. Moreover, we focus on three out of the four most intense geospace magnetic storms of solar cycle 24 that occurred in 2015, including the St Patrick's Day event, which is the strongest magnetic storm of the present solar cycle. We examine the associated ionospheric response at Swarm altitudes through the estimation of a Swarm Dst-like index. The newly proposed Swarm derived Dst index may be suitable for space weather applications. This article is part of the theme issue ‘Solar eruptions and their space weather impact’.